A tecelagem das margens: Por que tão solo? Dança e dramaturgia - Tarcisio dos Santos Ramos (2008)
This dissertation proposes to investigate the dramaturgy of the performance POR QUE TÃO SOLO?, created in Belo Horizonte/MG in 2006 by Marcenaria Centro de Criação Cênica as a result of the Klauss Vianna Dance Award granted by FUNARTE (National Art Foundation). Themain goal of the research is to identify the dramaturgic elements upon which the performance is built as well as discuss its dialogic character and the connections created during the creative process. Furthermore, the intention is to reveal the mechanisms that contributed to organizing the dramaturgy. In order to do so, the analysis will be supported by the articulation of concepts of dramaturgy in dance and dance-theater from the theoretizations and reflections developed by modern dance creators and contemporary researchers and artists, as well as concepts concerning theatrical semiology. The memory line of the dancing body is also a reference for reflecting about the dramaturgy created in POR QUE TÃO SOLO?. Finally, the dissertation proposes to define five structuring elements of the dramaturgy of the performance here analyzed, namely: the dancing body; the building of scenic-imagetic cells; the connection among the imagetic cores; the backdrop movement; the dramaturgy of the spectator.